In-Service Training Needs of Geography Teachers - (:unkn) unknown (MARMARA UNIV, 2016)
All professional groups are required to renew themselves, adapt and improve over time. Teachers also receive personal or corporate occupational training in order to develop and improve themselves. The Ministry of National Education, the employer of a large majority of teachers, carries out in-service training activities in order to contribute to the development of teachers. Prior to carrying out these activities, determining in-service training requirements of teachers is very important. Because a determination of needs is the main initiative required for the in-service training to be effective and efficient. This study has been carried out in order to determine in-service training needs of geography teachers, one of the branches of teaching. The study has been carried out with 210 geography teachers in the Istanbul province during the 2014-2015 academic years. The in-service training needs of geography teachers have been outlined and presented in the article.
Keywords: Geography teachers; in-service training